Belief as Faith：Taking Christianity as an Example - BI, Congcong (Journal of Research for Christianity in China (JRCC), 2023)
In daily language, faith has meanings such as sincerity, carefree, confidence, and piety; In religious language, faith refers to both trust in the divine, loyalty to religious organizations, and conviction in religious beliefs. Faith in Christianity has typical significance, referring to a strong, sustained, and reducible state of faith, as well as being associated with miracles and acts of love. In religious life, strong faith is expressed through speaking dialects, being gentle and moved, and trembling. As faith, Belief is integrated in the combination of beliefs and trust.